Killer elite : [the inside story of America's most secret special operations team] - Smith, Michael, 1952 May 1- (St. Martin's Press, 2007)
A top-secret U.S. Army Special Operations unit has been running covert missions all over the world, from leading death squads to the hideout of drug baron Pablo Escobar to assassinating key al Qaeda members, including Iraqi leader Abu Musab al-Zarqawi, and, in one of their greatest missions, capturing Saddam Hussein. ʺThe Activity,ʺ as it became known to insiders, has achieved near-mythical status, even among the worldʼs Special Operations elite. Now journalist Michael Smith gets inside this clandestine military team to expose their history and secrets. Michael Smith has spoken to many former members of the Activity, and we follow them on operations from the war on the drug barons that led Colombian ʺdeath squadsʺ to the hideouts of Pablo Escobar and his men. We learn of more recent missions, including snatching war criminals from their safe houses in the Balkans (at one time disguising themselves as French soldiers to lull a Serb warlord into a false sense of security), and operations in Iraq, Afghanistan, and the Horn of Africa.